Problems and Perspectives: a collection of new essays - Yolton,Jophn W. (ed.) (Cambridge, 1969)
This volume contains fourteen important essays on John Locke by scholars from a number of different fields: philosophy, history, political science and English literature. This collection represents some of the most recent research on his views on knowledge, belief and understanding, the economics of coinage, moral and political concepts and principles, science and the nature of the physical world.
Keywords: Political Science